Building a Community Organization: New Spaces for Social Change - Nadine Dolby (The University of Alabama, 2024)
In this critical reflection, I discuss my dual roles as a president of a local nonprofit organization and a full professor at my university. I reflect on how I moved from a volunteer at an animal shelter to a community leader, discuss the organization I founded in 2019, and explore the various, daily intersections between these two roles and experiences.